FUNDAMENTAL AND PRACTICAL INNOVATIVE RESEARCH IN MODERN LINGUISTICS («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article examines fundamental and practical innovative research in modern linguistics in the aspect of the communicative approach. The problems of the relationship between linguistics and related sciences are also considered, the importance of interdisciplinary studies of linguistic phenomena is emphasized. In the XXI century, all humanities, including linguistics, become different, since the modern social situation has placed new demands on them: first of all, it is a higher-level synthesis of sciences, their integrativity not only among themselves, but also with the natural sciences.
Keywords: integrativeness, anthropocentricity, communicativeness, dialogicality, cultural centricity, linguistics.